The effect of technique change on knee loads during sidestep cutting - Dempsey, A. R.; Lloyd, D. G.; Elliott, B. C.; Steele, J. R.; Munro, B. J.; Russo, K. A. (Medicine & Science in Sports & Exercise, 2007)
Purpose: To identify the effect of modifying sidestep cutting technique on knee loads and predict what impact such change would have on the risk of noncontact anterior cruciate ligament injury.